2004
DOI: 10.1093/geronb/59.2.p84
|View full text |Cite
|
Sign up to set email alerts
|

Practice and Drop-Out Effects During a 17-Year Longitudinal Study of Cognitive Aging

Abstract: Interpretations of longitudinal studies of cognitive aging are misleading unless effects of practice and selective drop-out are considered. A random effects model taking practice and drop-out into account analyzed data from four successive presentations of each of two intelligence tests, two vocabulary tests, and two verbal memory tests during a 17-year longitudinal study of 5,899 community residents whose ages ranged from 49 to 92 years. On intelligence tests, substantial practice effects counteracted true de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
208
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(225 citation statements)
references
References 43 publications
13
208
4
Order By: Relevance
“…44 In addition to linear trend terms the models also included dummy variables to account for practice effects, previously shown to be important in these data. 45 The statistical significance of terms in the regressions were obtained from adjusted Wald's tests. As vocabulary ability tends to remain relatively stable with age, longitudinal analysis was not performed on the MHA test.…”
Section: Discussionmentioning
confidence: 99%
“…44 In addition to linear trend terms the models also included dummy variables to account for practice effects, previously shown to be important in these data. 45 The statistical significance of terms in the regressions were obtained from adjusted Wald's tests. As vocabulary ability tends to remain relatively stable with age, longitudinal analysis was not performed on the MHA test.…”
Section: Discussionmentioning
confidence: 99%
“…The model has two levels, one at individual level including random intercept and random age effect, and the other a residual error. The methodological issues and notation of this model are discussed in detail elsewhere (Rabbitt et al 2004). This model examines how population average scores for each cognitive test vary with the effects of age, sex, occupational category, city of residence, year of entry (recruitment cohort) and practice (i.e.…”
Section: Analytical Modelmentioning
confidence: 99%
“…However, because more-able participants experience greater gains (Rabbitt et al 2001(Rabbitt et al , 2004, practice effects during longitudinal studies may selectively mask declines in individuals who are relatively more contented, and so more able, giving the misleading impression that less-able depressed individuals decline more rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…Even on the meta-analytic level, evidence is mixed regarding the effectiveness of cognitive training in both younger and older adults (e.g., Au et al 2015;Dougherty et al 2016;Karbach and Verhaeghen 2014;Kelly et al 2014;Lampit et al 2014;Melby-Lervåg and Hulme 2013;Melby-Lervåg et al 2016;Schwaighofer et al 2015;Soveri et al 2017). Aside from design and methodological choices potentially explaining the diverging findings (e.g., Noack et al 2009;Shipstead et al 2012), many authors increasingly articulated the potentially important influence of individual differences on cognitive training trajectories and outcomes (e.g., Buitenweg et al 2012;Guye et al 2016;Könen and Karbach 2015;Shah et al 2012;von Bastian and Oberauer 2014 Individual differences in cognitive functioning (e.g., Ackerman and Lohman 2006) and learning potential (e.g., Stern 2017) accentuate with increasing age (e.g., Rabbitt et al 2004) and have been shown to be related to personality (e.g., Graham and Lachman 2012), cognition-related beliefs such as need for cognition (NFC; e.g., Fleischhauer et al 2010;Hill et al 2013), and everyday life activities (e.g., Jopp and Hertzog 2007). Investigating which of these individual differences potentially predict cognitive training outcomes may not only explain inconsistencies concerning the effectiveness of cognitive training, but also identify possible subgroups of individuals that are more or less responsive to cognitive training, thereby constituting the conceptual groundwork for developing individually tailored interventions to boost training effectiveness.…”
mentioning
confidence: 99%
“…Individual differences in cognitive functioning (e.g., Ackerman and Lohman 2006) and learning potential (e.g., Stern 2017) accentuate with increasing age (e.g., Rabbitt et al 2004) and have been shown to be related to personality (e.g., Graham and Lachman 2012), cognition-related beliefs such as need for cognition (NFC; e.g., Fleischhauer et al 2010;Hill et al 2013), and everyday life activities (e.g., Jopp and Hertzog 2007). Investigating which of these individual differences potentially predict cognitive training outcomes may not only explain inconsistencies concerning the effectiveness of cognitive training, but also identify possible subgroups of individuals that are more or less responsive to cognitive training, thereby constituting the conceptual groundwork for developing individually tailored interventions to boost training effectiveness.…”
mentioning
confidence: 99%